Kajian Mutu Bakso Ikan Tuna yang Disubtitusi Tepung Karagenan - Sitepu, Moon Ayu Kawanari; Mewengkang, Hanny Welly; Makapedua, Daisy Monica; Damongilala, Lena Jeane; Mongi, Eunike Louisje; Mentang, Feny; Dotulong, Verly (Media Teknologi Hasil Perikanan, 2020)
Fishball is a fish product that knows for their distinctive taste and chewy texture. The quality of fishball greatly affects the attractiveness of consumers to consume it, regarding the taste and aroma. The ingredients of fishball that have properties as an emulsifying is carrageenan. The purpose of this study was to determine the quality of tuna fishballs substituted with carrageenan flour with different concentrations and storage times. The treatment design used was RAL (completely randomized design) which consisted of 4 different concentration treatments of added carrageenan, for 0%, 1%, 2% and 3% with 2 days of storage and 2 times repetition. The quality parameters were organoleptic test, water content, pH and TPC (Total Plate Count). The results showed that the addition of carrageenan affected the water content and pH of fishballs. Tuna fishballs with the addition of a concentration of 2% are the best products with an average value of organoleptic values: 6.58; water content: 71.63; pH: 5.46; and TPC: 2.6 × 10 4. Water content in fishballl is not met SNI quality requirements. Total bacteria (TPC) in fishballs met SNI quality requirements.Keywords: tuna fishballs, carrageenan